Elimination half‐life as a metric for the bioaccumulation potential of chemicals in aquatic and terrestrial food chains. (23rd May 2013) - Goss, Kai‐Uwe; Brown, Trevor N.; Endo, Satoshi
Abstract The assessment of chemicals as bioaccumulative in the regulatory process makes use of the bioconcentration factor as a metric. However, this metric does not account for the dietary uptake route and therefore cannot be applied to terrestrial food chains. In recent years, the biomagnification factor (BMF) and the trophic magnification factor (TMF) have been suggested as standard metrics for bioaccumulation. For regulatory purposes, though, the BMF and the TMF also suffer from a number of shortcomings. They are not applicable to assess uptake routes other than the diet (e.g., dermal uptake, as is important for personal care products). When measured in the field, they depend largely on biological and ecological factors and less so on the chemical's properties, and they are difficult to normalize and standardize. In the present study, the authors suggest the elimination half‐life (EL0.5) of a chemical as an alternative metric for bioaccumulation. The EL0.5 is equivalent to the depuration rate constant (k2) that is measured in various bioaccumulation and bioconcentration tests. This metric can be applied to air‐ and water‐breathing animals, and it is valuable for all uptake routes. It has a number of practical advantages over the BMF and the TMF. In combination with a standard uptake scenario, the EL0.5 can also be linked directly to a BMF threshold of unity. Thus, the EL0.5 as a bioaccumulation metric overcomes the shortcomings of the BMF and the TMF while still conserving the advantages of the latter metrics. Environ Toxicol Chem 2013;32:1663–1671. © 2013 SETAC